Buku Saku bagi Juru Bahasa Pemula “Mengenal Peranan Juru Bahasa Lebih Dekat" - Fauziah, Hanny (Jurnal Penerjemahan, 2015)
Interpreting is an oral/verbal translation activity, translating an oral message from the source language to the target language appropriate to the context and culture of the target language. There exist differences between translation and interpreting, namely in terms of time and faithfulness. In practice, in interpreting, the translator does not have the opportunity to use a dictionary or other reference materials when translation takes place due to time constraints (Gile, 1995: 112; Nababan, 2003: 116; Suryawinata & Hariyanto, 2003: 25). This book synopsis of “Community Language Interpreting” aims to help interpreters improve their ability in interpreting, be it in the community, business, or government sectors. This book written by Jieun Lee and Adrian Buzo presents an explanation on interpreters and interpreting in a plain language that is not convoluted, so that it is easily understood by readers, and beginning interpreters. Lee and Buzo explains that there are four methods of interpreting, namely consecutive (Consecutive Interpreting/CI), simultaneous (Simultaneous Interpreting/SI), dialogue (Dialogue Interpreting/DI), and sight translation. This book describes some aspects in relation to the definition of the transfer of language, interpreters, the procedure of the transfer of language, note-taking or recording techniques, the role of interpreters, ethics of interpreters, as well as some examples of dialogues in fields that often require the role of interpreters. The examples of texts presented in this book have managed to represent the four interpreting modes and can be used as training material for the NAATI accreditation/certification examinations, as well as a reference for interpreters, educators, and even students who are interested in studying and becoming interpreters. Keywords: interpreting, interpreter, interpreting modes